Penerapan Media Pembelajaran Berbasis Game Edukasi “Berangan” dalam Pembelajaran Puisi di SMK Negeri 2 Gowa - Masyuha, Hardianti Darwa (ppjbsip, 2025)
This study aims to describe the planning, implementation, and evaluation of the use of the educational game-based learning media